Insights into seafloor litter spatiotemporal dynamics in urbanized shallow Mediterranean bays. An optimized monitoring protocol using towed underwater cameras. (15th April 2022) - Fakiris, Elias; Papatheodorou, George; Kordella, Stavroula; Christodoulou, Dimitris; Galgani, Francois; Geraga, Maria
Abstract: Monitoring of marine litter at the sea surface, the beaches and the seafloor is essential to understanding their sources, pathways and sinks and design effective clean-up programs or increase public awareness for reducing litter waste. Up until today, seafloor litter is the least exploited component of marine litter. Although the protocols for recording and assessing seafloor litter in the deep-sea environments are currently being actively defined and practiced, shallow seafloor litter survey protocols are still notably under-developed. Moreover, trawling for fishing, which is the main means for collecting seafloor litter data, needs to be phased out in the coming years due to its high environmental footprint and be replaced by less destructive ways based on underwater imagery. In this paper we propose an integrated approach for assessing in detail the spatiotemporal distribution and composition of seafloor litter in shallow coastal environments, using common towed underwater cameras. Effort has been put to correctly estimating spatial litter densities regarding the true coverage of the visualized area, which was efficiently extracted through photogrammetric reconstruction of the seafloor. Interpretation of the spatial distribution of litter was aided by auxiliary bathymetric and swath sonar backscatter datasets, to determine the seabed geomorphological features that control their dispersion and composition. Local geo-morphology, along with any reported coastal anthropogenic activity, are correlated to seafloor litter densities to investigate the temporal and spatial dynamics that control their distribution and temporal trends in Syros Island, Cyclades, Greece. There, in the context of LIFE DEBAG project, monitoring of an urbanized shallow bay for 3 consecutive years has been performed to assess the impact of an intensive local awareness raising campaign to the local environment. A significant reduction of litter densities under the impact of this campaign has been documented, while links between the seafloor litter transport dynamics and the seabed micro- and macro-topography were made evident. Monitoring litter densities on the seafloor of urbanized shallow bays proved to be a prospective way of tracking marine litter pressures on the local marine environment. Highlights: A shallow benthic litter monitoring protocol, based on Towed Underwater Camera (TUC), is proposed and validated. The spatiotemporal benthic litter variations are linked to natural and anthropogenic drivers. Seabed morphology and seafloor hydrodynamics are shown to control litter accumulation. Significance of monitoring seafloor litter in urbanized bays: Narrowing sources and dynamics to comprehensible scales. First Proof of an awareness raising campaign ceasing marine litter pollution.